2016
DOI: 10.21462/jeltl.v1i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Students'ability in Writing Opinion Essay Using Flash Fiction

Abstract: <p>The use of literature in language classroom has attracted language teachers to utilize it in the FL classroom. This paper is intended to decribe the students’ ability to write opinion essay by using flash fiction, Frank Stocton’s <em>The Lady or the Tiger.</em> The design used in the study was content analysis design in which the researcher collected the students’ composition after they were assigned to write opinion essay by using flash fiction. The subject of the study was 2013A batch of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 5 publications
1
32
0
2
Order By: Relevance
“…In his dissertation, Hawthorne found that teachers of reluctant writers are alert to the interactions between the cognitive, behavioural and affective aspects of writing. Some other problems found in the teaching and learning of writing are: writing problems include they lack ideas, organizing of ideas, rhetoric or pattern of thought, cohesion and coherence (Nurhayati, 2016), students were able to make thesis statement that showed their opinion, but unable to develop the essay well (Setyowati, 2016), many students made a lot of mistakes in writing English, especially in using preposition and verb tenses and grammar structures (Huy, 2015), and low achievers were still confused in identifying the schematic structure of descriptive text and English Grammar (Siahaan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In his dissertation, Hawthorne found that teachers of reluctant writers are alert to the interactions between the cognitive, behavioural and affective aspects of writing. Some other problems found in the teaching and learning of writing are: writing problems include they lack ideas, organizing of ideas, rhetoric or pattern of thought, cohesion and coherence (Nurhayati, 2016), students were able to make thesis statement that showed their opinion, but unable to develop the essay well (Setyowati, 2016), many students made a lot of mistakes in writing English, especially in using preposition and verb tenses and grammar structures (Huy, 2015), and low achievers were still confused in identifying the schematic structure of descriptive text and English Grammar (Siahaan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As students engage in sentencecombining activities, they learn how to vary sentence structure in order to change meaning and style. Some researchers suggest that the appropriate techniques of writing should be implemented (Qomariyah & Permana, 2016;Noor, 2016;Ariyanti, 2016;Omar & Ghazali, 2016;Nurhayati, 2016;Setyowati, 2016;Lirola & Irwin, 2016). Shaughnessy (1977) and Hillocks (1986) suggest that sentence combining is an effective method to improve writing.…”
Section: E Discussionmentioning
confidence: 99%
“…To reach the teaching objectives of writing, the teacher must prepare and implement the appropriate teaching techniques (Irawati, 2015;Zuhri Dj & Sukarnianti, 2015;Qomariyah & Permana, 2016;Noor, 2016;Setyowati, 2016;Omar and Ghazali, 2016); Nurhayati, 2016) and some interactive media can be used, such as video (Nova, 2017).…”
Section: Discussionmentioning
confidence: 99%